2018
DOI: 10.3390/met8090700
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Embrittlement Susceptibility of R4 and R5 High-Strength Mooring Steels in Cold and Warm Seawater

Abstract: Hydrogen embrittlement susceptibility ratios calculated from slow strain rate tensile tests have been employed to study the response of three high-strength mooring steels in cold and warm synthetic seawater. The selected nominal testing temperatures have been 3 °C and 23 °C in order to resemble sea sites of offshore platform installation interest, such as the North Sea and the Gulf of Mexico, respectively. Three scenarios have been studied for each temperature: free corrosion, cathodic protection and overprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The cracks caused by EAC appear remarked in white, due to material deposition from the electrolyte in the areas of the substrate exposed by the appearance of the cracks themselves. Similar EAC cracking patterns had been observed in previous work [18] for steels with the same strength level as the GA-DH specimens, when a cathodic protection potential was applied to seawater immersed SSRT. can be considered as an actual effect of EAC and not a statistical artifact.…”
Section: Ga-dh Ga-sw 85% 72%supporting
confidence: 86%
See 1 more Smart Citation
“…The cracks caused by EAC appear remarked in white, due to material deposition from the electrolyte in the areas of the substrate exposed by the appearance of the cracks themselves. Similar EAC cracking patterns had been observed in previous work [18] for steels with the same strength level as the GA-DH specimens, when a cathodic protection potential was applied to seawater immersed SSRT. can be considered as an actual effect of EAC and not a statistical artifact.…”
Section: Ga-dh Ga-sw 85% 72%supporting
confidence: 86%
“…External hydrogen can be incorporated into the steel when the steel is working under high H 2 partial pressures [16] or under acidic conditions, among which sour service with H 2 S stands out and has led to the existence of a very specific regulation [17]. A more common source of external hydrogen is the intake from an electrolyte both when impressed current cathodic protection systems and sacrificial coatings are used (e.g., zinc plating or hot dip galvanizing) [18,19]. These processes involving external hydrogen leading to what is known as Environmentally Assisted Cracking (EAC).…”
Section: Introductionmentioning
confidence: 99%
“…The resistance reduction of each cell is carried out linearly between the following extreme conditions: • The resistance of the material is considered to fall linearly from 0% to 50% of its original resistance depending on the percentage of the diffusible hydrogen in solution, 0% and saturation condition, respectively. The maximum percentage of reduction has been taken arbitrarily from the maximum elongation reduction observed in the experimental work used for comparison (Artola et al, 2018). • When all the hydrogen in solid solution is trapped hydrogen, the original strength of the material is considered to remain intact.…”
Section: Integrated Embrittlement Modelmentioning
confidence: 99%
“…These tests are known as Slow Strain Rate Tensile tests (SSRT). Previous work by the authors, comparing a set of environmental conditions ranging from non-hydrogenating to strongly hydrogenating submerged seawater service, showed that SSRT can cause different cracking patterns depending on the studied steel, even for steels classified with the same strength grade (Artola et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…The microstructural state of the weld metal and the heat-affected zone is the most important factor in the mechanism of hydrogen embrittlement, cracking and reduction in impact toughness [ 5 , 6 ]. The desired fine-grained microstructure is often achieved in welding using an optimal thermal cycle [ 7 , 8 , 9 ] and through minimizing the content of impurities and segregations making the grain structure more refined [ 10 ].…”
Section: Introductionmentioning
confidence: 99%